APLIKASI PEMBELAJARAN ELECTRONIC LEARNING BERBASIS WEB: E-Learning;Internet;Phpmyadmin;SMK Jambi IX Lurah 2;Web. - Limia Budiarti, Rike; Puad, Lailyn; Tri Yolanda, Dimas (LP2M Universitas Nurdin Hamzah, 2021)
SMK Jambi IX Lurah 2 is one of the vocational high schools in Jambi Province, Indonesia. The learning system in SMK Jambi IX Lurah 2 is still carried out in a conventional way which is done face-to-face and is limited by place and time. Learning like this is less effective when there are holidays, red dates, sick students, teachers hold meetings and so on. With the existence of E-Learning, it is hoped that these problems can be resolved and learning takes place effectively. This E-Learning application is Web-based, made with the PHP programming language and MySQL database. In this E-Learning application the teacher uploads material and assignment questions, and students can see the assignments and materials that have been uploaded so that when students have uploaded the assignment, the teacher can assess the assignment. This application can provide value reports that can be accessed by teachers and can also make learning at SMK Jambi IX Lurah 2 more effective.